The eastern forest - Fielding, Eileen (New York : Benchmark Books, 1997)
Examines the forests of eastern North America, their ecosystems, and their responses to temperature and weather.
Includes bibliographical references (p. ) and index.
Keywords: Forest ecology -- East (U.S.) -- Juvenile literature; Forest ecology -- Canada, Eastern -- Juvenile literature; Forest ecology; Ecology